Peran Teknologi Informasi dan Sistem Operasional Bank Syariah pada SMK Hang Nadim Batam - Wasiman Wasiman (Universitas Pahlawan Tuanku Tambusai, 2021)
Community service is one form of the Tri Dharma of Higher Education that must be carried out by lecturers as a form of implementing knowledge possessed by schools, institutions or the surrounding community. The purpose of this community service is to provide an understanding of the information technology education process and provide an understanding of the operating system of Islamic banks. The method used in the service is the method of presentation and discussion of students at SMK Hang Nadim Batam. There are several majors at Hang Nadim Vocational School in Batam, such as the Department of Accounting, Light Vehicle Engineering, Electronics and Computers. The results of the service carried out are Increasing students' understanding of basic information technology and being able to use the technology; Students can distinguish the roles and functions of Islamic banks and conventional banks so that they can choose to use bank products and services in saving and investing or invest.